No escape from subsistence farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A small-scale farmer in South Africa describes the impact that economic liberalisation has had on his profitability, and calls on the government to assist farmers, otherwise they will never be able to move beyond subsistence farming.